A New Way to Promote Molecular Drug Release during Medical Treatment: A Polyelectrolyte Matrix on a Piezoelectric–Dielectric Energy Conversion Substrate. Issue 37 (16th August 2018) - Zhang, Yi; An, Qi; Tong, Wangshu; Li, Haitao; Ma, Zequn; Zhou, Yan; Huang, Tao; Zhang, Yihe
Abstract: Enhanced drug releases in a timely manner during urgent medical treatments would significantly enhance the prognosis of patients. Inspired by the facilitated molecular transports by the potentials, an enhanced drug release strategy driven by mechanical disturbances that widely exist in medical treatment processes is proposed. This strategy is enabled by a functional material comprised of multilayers of dendrimers as the drug reservoir, which are built on a piezoelectric–dielectric flexible film with reduced graphene oxide fillers. The generated voltages are higher and last longer than that in regular piezoelectric films. Photochemical crosslinking leads to a stable drug matrix which is even sustained in electric fields and high ionic strengths. The device enhances releases of positively, negatively, and zwitterionically charged molecules in response to mechanical stimuli and supports high cell viabilities. An illustrative application is demonstrated by preparing the material on the surface of a gastric lavage tube. The results show that the release of antiemetic drug increased by 200% within 60 min in response to forces mimicking human swallowing. This study contributes an integrative material that can realize electrically triggered releases that are previously only realized using complicated electrochemical setups. It is believed that this material can facilitate medicine applications in various emergent situations. Abstract : An enhanced drug release strategy driven by frequent and random mechanical disturbances that widely exist in emergent medical treatment processes is proposed. This strategy is enabled by a functional material comprised of a layer‐by‐layer film of dendrimers as the drug reservoir, which is built on a piezoelectric–dielectric flexible polymeric film.